1995
DOI: 10.1152/ajpheart.1995.268.2.h848
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic cardiac enkephalins inhibit vagal bradycardia in the dog

Abstract: Met-enkephalin-Arg-Phe (MEAP) has been identified in acid extracts of canine heart tissue. The effects of synthetic MEAP on the vagal control of heart rate were investigated in anesthetized dogs. The arterial infusion of MEAP (3 nmol.min-1.kg-1) inhibited the bradycardia observed during electrical stimulation of the right vagus nerve by 72%. After the infusion was stopped, the responsiveness to vagal stimulation returned to normal, with a half-time between 2 and 3 min. The inhibition by MEAP was reversed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
34
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 0 publications
4
34
0
1
Order By: Relevance
“…The case for the ␦ 1 -receptor is less clear because the pre-or postjunctional character of the response has not been addressed. However, no improved vagal function was noted when MEAP and methacholine were combined (8). The data thus far are, however, consistent with the hypothesis suggested by Crain and Shen (10) to explain the bimodal effects of opioids on the action potential duration in cultured dorsal root ganglion cells.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The case for the ␦ 1 -receptor is less clear because the pre-or postjunctional character of the response has not been addressed. However, no improved vagal function was noted when MEAP and methacholine were combined (8). The data thus far are, however, consistent with the hypothesis suggested by Crain and Shen (10) to explain the bimodal effects of opioids on the action potential duration in cultured dorsal root ganglion cells.…”
Section: Discussionsupporting
confidence: 89%
“…The vagolytic response was presumed to be mediated through the prejunctional inhibition of acetylcholine release. This assumption was based on the failure of MEAP to alter the bradycardia following the addition of the direct-acting cholinergic methacholine (8). Although the ␦ 2 -receptor is probably located on the vagal nerve terminals, MEAP may act indirectly on an intermediate cell or interneuron.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative significance of individual endogenous enkephalins is also unclear. Although all the endogenous enkephalins are qualitatively ␦-agonists, MEAP may be more potent in some respects, perhaps in part because of a slower rate of degradation (6,7,19). Despite potential differences, however, all three enkephalins evaluated in the present study were cardioprotective when added exogenously.…”
Section: Discussionmentioning
confidence: 99%
“…In the canine heart, MEAP interrupted vagal transmission within the sinoatrial (SA) node at a site proximal to the muscarinic receptors resident on the pacemaker cells (5,14). Extensive agonist/antagonist profiles indicated that the receptors responsible for these observations are ␦ 2 -opioid receptors (15,20).…”
mentioning
confidence: 99%